Sinau Bareng With Cak Nun And Kiai Kanjeng In Religious Diversity Perspective (Case Study Of Sinau Bareng Activities Implementation In Batu Malang City 41177 Edition) - Yuni Suprapto; Wasino Wasino; Thiwaty Arsal; At. Sugeng P (International Conference on Science, Education, and Technology, 2022)
Sinau Bareng with Cak Nun and Kiai Kanjeng (CNKK), an interesting phenomenon when Sinau Bareng activity with CNKK on 41177 editions in Batu Malang City, there was a Transgender attending the recitation, it was very rare, the authors are interested in dissecting it using a diversity perspective. Cak Nun responded to Mirel phenomenon that he has gave the congregations with attitude of a verse in Qur’an; ya ayyuhan naas inna kholaqnakum min dzakarin wa untsa wa ja’alanakum syu’uban wa qabaaila lita’arafuu, that Allah created humans with male and female potential. As stated in the verse; zakarin (manlike), not mudzakkarin (male). According to the author, the value taken from the events of Sinau Bareng with Cak Nun and Kiai Kanjeng 4117 editions in Batu Malang, is that we should not consider and discriminate other people or humans by assuming that we are superior to others. The analysis of diversity and social studies is that the Sinau Bareng activity with Cak Nun and Kiai Kanjeng (CNKK) accommodates the substantive of diversity value; from a humanitarian point of view. The conclusions of quantitative and qualitative social analysis, that; Malang Community – Mirel (Transgender) = Negative (Does not accommodate Diversity) CNKK - Jamaah Maiyah (recitation) = Positive interaction (accommodates diversity) with members from various backgrounds and social statuses. Mirel – Environment = Positive Interaction (planting orchids and releasing shrimp in the river, able to preserve the environment). CNKK - Mirel = Positive Interaction (accept Mirel As a human being that the same as other).